Effects of Fe doping on enhancing electrochemical properties of NiCo2S4 supercapacitor electrode. (20th April 2020) - Phonsuksawang, Praphaiphon; Khajondetchairit, Patcharaporn; Butburee, Teera; Sattayaporn, Suchinda; Chanlek, Narong; Hirunsit, Pussana; Suthirakun, Suwit; Siritanon, Theeranun
Abstract: NiCo2 S4 have been widely studied as electrode materials for supercapacitors. Several strategies, including the morphology controls and elemental doping, have been used to improve its performance. This research investigates the effects of FeCl3 addition on structure, morphology, and electrochemical performance of NiCo2 S4 prepared by a one-step hydrothermal method. FeCl3 plays two important roles. It affects the synthetic condition which consequently influences the morphology and acts as a source of Fe 3+ which is incorporated in NiCo2 S4 lattice. Remarkably, the Fe-added electrode shows significantly improved performance with high specific capacity of 167 mAh/g at current density of 10 A/g, which is ∼170% enhancement compared with that of the electrode without FeCl3 addition. Detail analyses on electrochemical behavior and theoretical computations reveal that the enhanced performance is caused by the improved electrical conductivity as evidenced by electrochemical impedance spectroscopy (EIS) and the increased density of states (DOS) at the Fermi level. In addition, the doped system could facilitate OH − adsorption on the material surface which benefits the electrochemical reaction. The obtained results give insight to the roles of metal doping in NiCo2 S4 electrode which could be helpful in the future development of this material. Graphical abstract: Image 1